A Multilevel Model of Safety Climate: Cross-Level Relationships Between Organization and Group-Level Climates. - Zohar, Dov; Luria, Gil (Journal of Applied Psychology, 2005)
Organizational climates have been investigated separately at organization and subunit levels. This article tests a multilevel model of safety climate, covering both levels of analysis. Results indicate that organization-level and group-level climates are globally aligned, and the effect of organization climate on safety behavior is fully mediated by group climate level. However, the data also revealed meaningful group-level variation in a single organization, attributable to supervisory discretion in implementing formal procedures associated with competing demands like safety versus productivity. Variables that limit supervisory discretion (i.e., organization climate strength and procedural formalization) reduce both between-groups climate variation and within-group variability (i.e., increased group climate strength), although effect sizes were smaller than those associated with cross-level climate relationships. Implications for climate theory are discussed.